Journal Of Applied Aquaculture - Journal Of Applied Aquaculture (Taylor & Francis, 2026)
The Journal of Applied Aquaculture is a platform for sharing practical information that is essential for researchers to meet the needs of investors, farm managers, extension agents and policy makers working to adapt aquaculture theory to achieve economic and food security objectives throughout the world. The journal emphasizes multi-disciplinary research and case studies that propose financially and logistically viable solutions to observable problems. To make it more accessible to farmers and non-specialists in addition to professional aquaculture researchers, authors publishing in the Journal of Applied Aquaculture are requested to avoid basic research that has only downstream or marginal applicability to actual farming systems. Technical jargon should be kept to a minimum. Tables and figures that facilitate comprehension are encouraged. An economic and feasibility analysis should accompany any proposed technological innovation. Both original research and reviews will be considered.
FI 0.46
Q3
Keywords: Biological; Earth & Environmental Food Science; Acuicultura; Acuerdos transformativos; Transformative agreements; Ciencia ambiental; Gestión del agua; Calidad genética